The Consolidation of Chinese Private Higher Education - Yu, Kai (International Higher Education, 2018)
China is the world’s largest higher education market, and higher education has become a key area for investment in China. The private higher education industry in the country, which is highly fragmented at the moment, is expected to undergo a wave of consolidation over the next decade, with the objectives of ensuring continued growth and impact, greater efficiency, greater economies of scale, and improved quality, reputation, and competitiveness.